Dimensions of Safety Practices in Educational Institutions: A Scoping Review Toward Boarding School Adaptation - Phuspa, Sisca Mayang; Arifah, Dian Afif; Diannita, Rindang; Yaakub, Norwahida; Ramli, Azizan; Hanifah, Mohd Shahril Abu; Osman, Azim Azuan; Razak, Nur Fazhilah Abdul (Universitas Airlangga, 2025)
Introduction: The safety of educational institutions, especially at boarding schools, remains an underexplored area in safety management research. This scoping review aims to identify key dimensions of safety practices in educational institutions to provide a foundational framework for adapting safety assessments to boarding schools. Methods: Through the JBI’s Framework, a comprehensive search of six databases (PubMed, CORE, DOAJ, ScienceDirect, Wiley, and SAGE Journals) yielded 240 articles. After applying inclusion and exclusion criteria, 14 articles were included in the final analysis. Results: Content analysis of these articles revealed four main categories of school safety guidelines: structural and environmental aspects (16 indicators), knowledge aspects (15 indicators), behavioral aspects (13 indicators) and social support aspects (10 indicators). Structural and environmental aspects primarily focused on physical facilities and infrastructure. Knowledge aspects focused on the content of safety education materials that students and teachers must understand. Behavioral aspects focus on daily activities in the educational environment that support a safe culture. Social support focused on the involvement of parties outside the educational institution to support a safety culture. Conclusions: Although none of the reviewed studies focused specifically on boarding schools, the identified dimensions offer a useful starting point for developing a culturally relevant safety assessment tool. This review highlights the lack of context-specific literature and the need for further research, including expert consultation and field validation, to ensure effective safety strategies in boarding school settings.